Circadian rhythm phase shifts caused by timed exercise vary with chronotype - Thomas, J. Matthew (JCI Insight, 2020)
BACKGROUND: The circadian system entrains behavioral and physiological rhythms to environmental cycles, and modern lifestyles disrupt this entrainment. We investigated a timed exercise intervention to phase shift the internal circadian rhythm. METHODS: In 52 young, sedentary adults, dim light melatonin onset (DLMO) was measured before and after 5 days of morning (10 hours after DLMO; n = 26) or evening (20 hours after DLMO; n = 26) exercise. Phase shifts were calculated as the difference in DLMO before and after exercise. RESULTS: Morning exercise induced phase advance shifts (0.62 ± 0.18 hours) that were significantly greater than phase shifts from evening exercise (–0.02 ± 0.18 hours; P = 0.01). Chronotype also influenced the effect of timed exercise. For later chronotypes, both morning and evening exercise induced phase advances (0.54 ± 0.29 hours and 0.46 ±0.25 hours, respectively). In contrast, earlier chronotypes had phase advances from morning exercise (0.49 ± 0.25 hours) but had phase delays from evening exercise (–0.41 ± 0.29 hours). CONCLUSION: Late chronotypes — those who experience the most severe circadian misalignment — may benefit from phase advances induced by exercise in the morning or evening, but evening exercise may exacerbate circadian misalignment in early chronotypes. Thus, personalized exercise timing prescription, based on chronotype, could alleviate circadian misalignment in young adults. TRIAL REGISTRATION: Trial registration can be found at www.clinicaltrials.gov (NCT04097886). FUNDING: Funding was supplied by NIH grants UL1TR001998 and TL1TR001997, the Barnstable Brown Diabetes and Obesity Center, the Pediatric Exercise Physiology Laboratory Endowment, the Arvle and Ellen Turner Thacker Research Fund, and the University of Kentucky.